Elemental - Vaughan-Lee, Emmanuel; Roshan, Gayatri (United States, 2012)
The film follows three outsiders who are obsessed by nature and driven by a deep desire to change the status quo. Rajendra Singh, an Indian government official gone rogue, mounts a national crusade to save the Ganges River. Activist Eriel Deranger leads a David and Goliath fight against the oil giants who are destroying her homeland in the Canadian Tar Sands. Australian inventor, Jay Harman, is attempting to halve the world's energy consumption by mimicking natural systems. Separated by continents, each character is part of a global story about water and climate change that goes beyond the issues to reveal the public triumphs and emotional scars of life on the front line.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films